Requirement for d(GATC) sequences in Escherichia coli mutHLS mismatch correction. - Lahue, R S (1987)
The involvement of d(GATC) sequences in Escherichia coli DNA mismatch correction was ascertained by analyzing in vitro repair efficiencies of a series of related, covalently closed circular DNA heteroduplexes that contained from zero to four d(GATC) sites. A heteroduplex with four d(GATC) sites was repaired with high efficiency by extracts of E. coli, whereas no significant correction occurred on a closely related molecule lacking such sequences. Heteroduplexes containing one or two d(GATC) sites were corrected at rates between 10% and 93% of that observed for the four-site molecule, but repair efficiency did not correlate in a simple way with the number of sites present. The methylation state at a single d(GATC) sequence was sufficient to direct strandedness of repair, and correction of heteroduplexes containing one or more d(GATC) sites required functional mutH, mutL, and mutS gene products. In addition, DNA repair synthesis dependent on mutH and mutS also required the presence of at least one d(GATC) site. Although mismatch correction was not observed on a covalently closed circular heteroduplex lacking a d(GATC) sequence, such molecules were subject to strand-specific repair if they contained a strand-specific single-strand break. However, this correction reaction did not require mutH, mutL, mutS, or uvrD gene products. Consequently, we have concluded that d(GATC) sequences are directly involved in mismatch correction mediated by the mutHLS system.